The Effect of Literacy based on Exploration of Science with Cultural Insights on Thematic Content Mastery and Social Attitude (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aimed to analyze the effect of literacy learning with cultural insight on science learning outcomes and the social attitudes of students in elementary schools. This research was a quasi-experimental study using a non-equivalent post-test only control group design. The population of this study was 140 students, while the sample was selected by random sampling. The number of samples in this study was 100 students who were divided into two classes. The instrument used was a test of learning outcomes in the form of multiple-choices and social attitude questionnaires. Validation of the learning outcomes instrument used content validity with the Gregory test, and item validity used biserial point correlation, the reliability of the test used KR-20, different power, and difficulty level. Meanwhile, validation on social attitude instruments used content validity with the Gregory test, item validity was used product-moment correlation, and test reliability was used KR-20. The data collected were analyzed by Multivariate Analysis of Variance. The results showed that the results of the significance of all three hypotheses are 0,000, which means less than 0.05 (0,000 0.05). So, it can be concluded that there was a positive effect of literacy based on the exploration of science with cultural insights on thematic content mastery and social attitude. The novelty of this research integrates literacy learning with Balinese cultural insight on science learning outcomes and social attitudes.